Advances in water jetting : Selected Papers from the International Conference on Water Jet 2019 - Research, Development, Applications, November 20-22, 2019, Čeladná, Czech Republic /: Selected Papers from the International Conference on Water Jet 2019 - Research, Development, Applications, November 20-22, 2019, Čeladná, Czech Republic. ([2021]) - Unknown
No abstract available